Analysis of River Blocking Induced by a Debris Flow. (28th September 2017) - Wang, Lijuan; Chang, Ming; Dou, Xiangyang; Ma, Guochao; Yang, Chenyuan
Abstract : Both the Wenchuan earthquake on May 12, 2008, and the Lushan earthquake on April 12, 2013, produced many coseismic landslides along the Nanya River in Shimian City. Subsequent debris flows that initiated from these landslides and are triggered by intense rainfall become the secondary hazard in the years after the earthquake; in particular, some debris flows led to a serious river blocking event. For example, the Guangyuanbao debris flow which occurred on July 04, 2013, partly blocked the Nanya River, presenting a major threat to the national highway and residential areas. To analyze the pattern of landslide damming, we analyzed numerical simulations of the movement characteristics of the Guangyuanbao debris flow using rainfall intensities with varying recurrence periods of 5, 20, and 50 years. The accuracy of the spreading of the numerical simulation is about 90%. The simulation indicated a small volume of sediment entering the river for a rainfall under 5-year return period. A debris flow induced by rainfall under 20-year return period partly blocked the river, while rainfall under 50-year return period has potential to block the river completely. This proposed analysis of river blocking induced by a debris flow could be used for disaster prevention in earthquake-stricken area.